Effects of two different robot-assisted arm training on upper limb motor function and kinematics in chronic stroke survivors: A randomized controlled trial. Issue 4 (19th May 2021) - Cho, Ki-Hun; Song, Won-Kyung
ABSTRACT: Background: Comparative studies of different robotic types are warranted to tailor robot-assisted upper limb training to patient's functional level. Objectives: This study aimed to directly compare the effects of high inertia robot arm (whole arm manipulator, WAM) and low inertia robot arm (Proficio) on upper limb motor function in chronic stroke patients. Methods: In this randomized controlled trial, 40 chronic stroke survivors were randomized into robot-assisted arm training with WAM (RAT-WAM) and robot-assisted arm training with Proficio (RAT-P) groups. The RAT-WAM and RAT-P groups participated in the robot-assisted arm training with WAM and robot-assisted arm training with Proficio, respectively, for 40 min daily, three times weekly over a four week. Upper limb motor function was measured before and after the intervention using the Fugl–Meyer assessment (FMA), action research arm test, and box and block test (BBT). Curvilinearity ratio (the length ratio of a straight line from the start to the target) was also measured as an index for upper limb kinematic performance. Results: The RAT-WAM and RAT-P groups showed significant improvements in FMA-total and -proximal (shoulder/elbow units), BBT, and ARAT after the intervention ( P < .05). Also, the RAT-P group showed significantly more improvement than the RAT-WAM group in FMA-distal (hand/wrist units) ( P < .05). Conclusions: Improvements of upper limb motor function occurred during robot-assisted arm training with robotic systems. Low inertia robot arm was more effective in improving the motor function of the hand and wrist. The results may be useful for robot-assisted training for upper limb impairment.